Drug delivery engineering principles for drug therapy - Saltzman, W. Mark (Oxford University Press, 2001)
This text is a synthesis of the principles that govern rates of drug transport, reaction, and disappearance in physiological and pathological situations, providing a working foundation for those in the field of drug delivery. The book covers advanced drug delivery and contemporary biomaterials.
Keywords: Drug delivery systems.; Biomedical materials.; elektronické knihy; electronic books